Patient-reported outcome measures and value-based medicine in paediatrics: a timely review - Yi Hua Tan; Jia Xuan Siew; Biju Thomas; Kee Chong Ng (Singapore Medical Journal)
Healthcare delivery is moving towards a more personalised and patient-centric approach. There is now an appropriate emphasis on providing value in our healthcare system. Patient-reported outcome measures (PROMs) assess our patients’ perceptions of the status of their health and quality of life, measured over a period of time. PROM is an integral component of a value-driven and value-based healthcare system and is key if we want to practise value-based medicine. In paediatrics and child health, PROMs, if implemented well with appropriate measurement tools that are regularly updated and validated in a self-learning healthcare ecosystem, will help to enhance personalised healthcare delivery and collectively improve the health of the community at large. This review covers the role of PROMs in paediatrics, as well as their role in value-based medicine.